2019
DOI: 10.2109/jcersj2.19103
|View full text |Cite
|
Sign up to set email alerts
|

First-principles energy band calculation of a (Ca<sup>2+</sup>, V<sup>5+</sup>)-doped Y<sub>2</sub>Ti<sub>2</sub>O<sub>7</sub> pigment

Abstract: A first-principles energy band calculation is performed with respect to the V 5+-and (Ca 2+ , V 5+)-doped Y 2 Ti 2 O 7 supercells to elucidate the effect of Ca 2+ doping on the electronic structure and optical properties of a V 5+-doped Y 2 Ti 2 O 7 pigment in the present study. The structural optimization calculation reveals that the theoretical lattice constant of the Y 2 Ti 2 O 7 unit cell slightly increases when compared with that in the experimental data. The forbidden gap at the ¥ point is estimated to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…For both undoped and Bi-doped samples, the wave-vector k, that is, the momentum is the same for the maximum energy of the valence band and the minimum energy of the conduction band (Figure S7), which indicates the direct band gap of the samples. The PBE-calculated band gap of the YTO is 2.82 eV (22,728 cm –1 ), which agrees well with computed results reported previously. , However, this value is apparently much underestimated compared to any reported experimental results as listed above. It is well known that the GGA-based approximation method tends to underestimate band gaps, especially those of transition metal oxide systems.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…For both undoped and Bi-doped samples, the wave-vector k, that is, the momentum is the same for the maximum energy of the valence band and the minimum energy of the conduction band (Figure S7), which indicates the direct band gap of the samples. The PBE-calculated band gap of the YTO is 2.82 eV (22,728 cm –1 ), which agrees well with computed results reported previously. , However, this value is apparently much underestimated compared to any reported experimental results as listed above. It is well known that the GGA-based approximation method tends to underestimate band gaps, especially those of transition metal oxide systems.…”
Section: Resultssupporting
confidence: 91%
“…The PBE-calculated band gap of the YTO is 2.82 eV (22,728 cm −1 ), which agrees well with computed results reported previously. 60,61 However, this value is apparently much underestimated compared to any reported experimental results as listed above. It is well known that the GGA-based approximation method tends to underestimate band gaps, especially those of transition metal oxide systems.…”
Section: Band Structures Of the Yto And Ytobmentioning
confidence: 61%
“…Three types of convergence criteria, that is, the total energy, charge, and force, were used for each self-consistent field-cycle and set to 0.0001 Ry for at least three iterations; 0.001e for the last iteration; and 1.0 In the present study, we assumed that the valences of the doped atoms, M and V, are trivalent and pentavalent, respectively, for the (M,V)-doped ZrO 2 supercells, whereas for the V-doped and M-doped ZrO 2 supercells, we assumed that V and M are tetravalent and trivalent, respectively. 10) As for (M,V)-doped ZrO 2 , there are no reported cases of V valence in ZrO 2 , but it is confirmed that V is present at +4 in ZrO 2 doped only with V. 4)…”
Section: Methodsmentioning
confidence: 87%
“…Also, we constructed another (M,V)-doped supercell in which the MV distance is longer; however, the total energy of the latter (M,V)-doped supercell increased in comparison with that of the former (M,V)-doped supercell. 10) Therefore, we used the calculation data for the former (M,V)doped supercell in the present study.…”
Section: Methodsmentioning
confidence: 99%